#TITLE_ALTERNATIVE# - KURNIAWAN DUHA (NIM : 12210011), DANY
Gas plateau rate is one important thing to be agreed in oil and gas cooperation contract between contractor, Government, and buyer because those three sides have different interest. Contractor want gas recovery factor as high as possible in the early phase of production with as high as possible gas plateau rate because it will give higher Net Present Value (NPV) and Rate of Return (ROR). Depend on that condition, remaining reserve will be lower and this condition is undesirable by Government. Government want gas remaining reserve to be produced as high as possible, thus the plateau rate must be as low as possible. In this study, Recovery Factor (RF) for contractor is called Contractor Concern Recovery Factor (CCRF) which is gas recovery in contract time. While the remaining reserve after contract end which is Government concern is called Government Concern Recovery Factor (GCRF). Based on writerÃ‚Â’s hypothesis, win-win gas plateau rate concept for contractor and Government is intersection between CCRF and GCRF to ROR. To observe influence of parameters for recovery factor and gas plateau rate, this final project had already built gas field reservoir model from field data. By using that gas field reservoir model, sensitivity test to recovery factor is done to porosity standard deviation, permeability heterogenity, residual gas saturation, and gas plateau rate. Sensitivity test to gas plateau rate is done to gas residual saturation, Corey exponent, average permeability, Original Gas In Place (OGIP), and contract time. Design of Experiment (DoE) method is done two times to observe level of influence those parameters to recovery factor and gas plateau rate. Then level of influence to recovery factor which are listed in order are gas plateau rate, permeability heterogenity, residual gas saturation, and porosity standard deviation. Level of influence to gas plateau rate which are listed in order are OGIP, contract time, relative permeability, Corey exponent, and gas residual saturation.